(untitled) (REMUNOM, 2025)
Introduction: Cervical cancer (CCU) is considered a major public health problem and one of the most common tumors in the female population. Pharmaceutical intervention should complement medical services by informing cancer patients about the purpose of antineoplastic drugs and supportive therapy, mentioning adverse events and possible drug interactions. Objectives: To describe the role of pharmaceutical intervention in the prevention and pharmacological care of cervical cancer. Methodology: This study was a literature review. For the elaboration of this article, studies will be searched and selected through the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), and PubMed. Studies conducted between 2015 and 2025 were selected. Results and Discussion: Cervical cancer is a disease that affects women globally. According to INCA (Brazilian National Cancer Institute), it represents the third most common neoplasm among women in Brazil. Based on the studies presented, it is observed that gynecological cancers continue to have a high incidence in Brazil. Furthermore, the frequently late diagnosis hinders adequate access to health services and highlights, above all, the insufficiency in terms of quantity and quality of care provided for the treatment of these cases outside of major cities. Conclusion: Finally, cervical cancer remains one of the major challenges to public health, especially in developing countries like Brazil, where socioeconomic, cultural, and structural aspects hinder access to information, preventive actions, and early diagnosis.